1992
DOI: 10.1007/bf00170082
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the distribution and regulation of microbial keto ester reductases

Abstract: In a limited screening 65 microorganisms were tested with regard to their ability to reduce keto acids or esters of different chain length and position of the keto group with NADH or NADPH as coenzymes. Twentyseven organisms exhibited reductase activity. Among these, Candida parapsilosis and Rhodococcus erythropolis have been chosen for further investigation. The keto ester reductases of both C. parapsilosis and R. erythropolis prefer NADH as coenzyme and show higher activity towards keto esters than keto acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Further biochemical assay demonstrated that Fusarium KivRFp could utilize NADPH and NADH as coenzyme, while the NADPH is preferred (Figure 5 B). In accordance to our results, bacterial chiral enzymes belonging to the D-ketoacid reductases superfamily also could utilize NADH as coenzyme, and also feature a conserved Arg-(Asp/Glu)-His active site triad [ 20 , 37 ]. Based on the phylogenetic, molecular, and biochemical analysis results, we propose that KivRFp is a new member of family ketonate oxidoreductases.…”
Section: Discussionsupporting
confidence: 86%
“…Further biochemical assay demonstrated that Fusarium KivRFp could utilize NADPH and NADH as coenzyme, while the NADPH is preferred (Figure 5 B). In accordance to our results, bacterial chiral enzymes belonging to the D-ketoacid reductases superfamily also could utilize NADH as coenzyme, and also feature a conserved Arg-(Asp/Glu)-His active site triad [ 20 , 37 ]. Based on the phylogenetic, molecular, and biochemical analysis results, we propose that KivRFp is a new member of family ketonate oxidoreductases.…”
Section: Discussionsupporting
confidence: 86%
“…The FDH catalyzes the oxidation of formate into carbon dioxide, while reducing the oxidized form of the cofactor into its reduced form, NAD(P)H. The most widely applied FDH is probably the FDH from C. boidinii and optimized mutants thereof [191] developed in the Kula group who are --jointly with the Hummel and Wandrey groups --pioneers in the fi eld of FDH -based applications [192,193] in addition to the Whitesides group [194] . The Kula group also carried out preparative transformations based on these enzymes by coupling the ADH reduction reactions with FDH regeneration [198,199] . In addition, downstream processing is simplifi ed since (ideally) no organic by -product remains in the reaction mixture.…”
Section: Reduction Of Ketonesmentioning
confidence: 99%
“…NAD-dependent coniferyl alcohol dehydrogenase (Jaeger et al, 1981 ;Jaeger, 1988), NAD\mycothiol-dependent for-maldehyde dehydrogenase (Eggeling & Sahm, 1984van Ophem et al, 1992 ;van Ophem & Duine, 1994 ;Misset-Smits et al, 1997) and methanol : N,Ndimethyl-4-nitrosoaniline (NDMA) oxidoreductase (MNO) from R. erythropolis DSM 1069 (van Ophem et al, 1993) ; MNO from R. rhodochrous LMD 89.129 (van Ophem et al, 1993) and from Rhodococcus sp. NI86\21 (Nagy et al, 1995), which has since been identified as R. erythropolis (de Schrijver et al, 1997) ; NAD-dependent propan-2-ol dehydrogenase from R. rhodochrous PNKb1 (Ashraf & Murrell, 1990, 1992 ; NADH-dependent carbonyl reductase from R. erythropolis DSM 743 (Peters et al, 1992(Peters et al, , 1993Zelinski et al, 1994) ; NAD-dependent long-chain secondary alcohol dehydrogenase from R. erythropolis ATCC 4277 (Ludwig et al, 1995) ; NAD-dependent secondary alcohol dehydrogenase from Rhodococcus sp. GK1 (Krier et al, 1998).…”
Section: Introductionmentioning
confidence: 99%